Through the Looking Glass of Culture: Unravelling the Intentions Behind Green Hotel Visitation Using Hunt-Vitell Theory - Asif, Fizza; Khan, Muhammad Ishfaq (Migration Letters, 2024)
The purpose of this research is to examine the relationship between tourists’ cultural factors (collectivism and long-term orientation) and their intention to visit green hotels, with a particular focus on the sequential mediation of both ethical philosophy and ethical judgement. Using the Hunt-Vitell theory of marketing ethics, the study develops a prediction model and analyzes it through PLS-SEM on a sample of 485 Pakistani tourists calculated using the G* power calculator. The findings demonstrate that tourists’ cultural factors have a significant positive relationship with their intention to visit green hotels and that ethical philosophies and ethical judgement positively mediate this link. This research offers valuable insights for industry practitioners and researchers in the hospitality sector, expanding our understanding of the intricate interplay between culture, marketing ethics, ethical philosophy, and green hotels in a developing economy.